Specific association of the proto-oncogene product pp60c-src with an intracellular organelle, the PC12 synaptic vesicle (The Rockefeller University Press, 1992)
The protein product of the proto-oncogene c-src is a membrane- associated tyrosine kinase of unknown function. Identification of pp60c- src target membranes may elucidate the function of the c-src protein. The available evidence indicates that pp60c-src associates with distinct membranes within single cell types and has different distributions in different cell types. Our experiments demonstrate targeting of pp60c-src to an isolatable and biochemically identified membrane fraction in the neuroendocrine cell line PC12. The c-src protein was found to be specifically associated with synaptic vesicles since: (a) the pp60c-src immunofluorescent pattern overlapped with a synaptic vesicle marker, synaptophysin; (b) a significant proportion (44%) of the pp60c-src from PC12 but not fibroblast postnuclear supernatants was recovered in a small vesicle fraction; (c) an anti- synaptophysin cytoplasmic domain antibody immunodepleted all of the pp60c-src vesicles in this fraction, and (d) pp60c-src copurified during a 100-fold purification of PC12 synaptic vesicles. These results suggest a role for the c-src protein in the regulation of synaptic vesicle function.